Subjects of Interest: Biography, Politics and Gender History - Brooke, Stephen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
This article discusses the biographical genre in history in the light of recent trends in gender and cultural history. It suggests that biography has the possibility of building on the strengths of these developments, but only through a resistance to the temptations of authoritative meta-narrative. Instead, it points to the creative unevenness of lives and the potential of using that ambiguity to describe in more interesting and creative ways both the lives of individual subjects and the connections between those individuals and larger collective identities. The argument reviews the work of authors such as Becky Conekin, Sheila Rowbotham and Carolyn Steedman.